2019
DOI: 10.1111/andr.12737
|View full text |Cite
|
Sign up to set email alerts
|

Increasing paternal age and ejaculatory abstinence length negatively influence the intracytoplasmic sperm injection outcomes from egg‐sharing donation cycles

Abstract: Background:The paternal role in embryogenesis is much more than providing a haploid genome. The spermatozoa have crucial roles related to embryogenesis' epigenetic regulation, fusion of gametes, and cleavage, which may influence intracytoplasmic sperm injection outcomes. Objectives:To study whether paternal age, length of ejaculatory abstinence and semen parameters influence the outcomes of intracytoplasmic sperm injection in the oocyte recipients from egg-sharing donation cycles. Materials and methods:This hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 58 publications
4
21
0
Order By: Relevance
“…Furthermore, an association has been observed between short abstinence and outcomes in various Assisted Reproduction Techniques (IUI, IVF, ICSI) 10,17 . Shorter abstinence time also seems to be related to increased pregnancy rates, embryo quality on day 3, blastocyst development and implantation following assisted reproduction 18–20 . Over many years of experience, we have observed that a second semen sample produced after a short time has different parameters, including a better motility.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, an association has been observed between short abstinence and outcomes in various Assisted Reproduction Techniques (IUI, IVF, ICSI) 10,17 . Shorter abstinence time also seems to be related to increased pregnancy rates, embryo quality on day 3, blastocyst development and implantation following assisted reproduction 18–20 . Over many years of experience, we have observed that a second semen sample produced after a short time has different parameters, including a better motility.…”
Section: Introductionmentioning
confidence: 89%
“…10,17 Shorter abstinence time also seems to be related to increased pregnancy rates, embryo quality on day 3, blastocyst development and implantation following assisted reproduction. [18][19][20] Over many years of experience, we have observed that a second semen sample produced after a short time has different parameters, including a better motility. Supported by the literature, we started this study with the aim of verifying if it could be a good strategy to gain more motile spermatozoa for successful intracytoplasmic sperm injection (ICSI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we found no significant association between sexual abstinence periods before ICSI and fertilization rate after the procedure. There are several studies with the same results in this regard (Colturato et al, 2007;Lee et al, 2015;Periyasamy et al, 2017;Borges Jr et al, 2019;Setti et al, 2020). Lee et al (2015) in a retrospective study have evaluated fertilization and pregnancy outcomes of 131 fresh ICSI cycles regarding different abstinence periods (2-4 days vs. 5-7 days).…”
Section: Multivariable Linear Regression Analysis Ofmentioning
confidence: 99%
“…However, several of the preceding studies have indicated the sexual abstinence period was associated with embryo development and pregnancy outcomes after the ICSI procedure (Colturato et al, 2007;Periyasamy et al, 2017;Borges Jr et al, 2019;Setti et al, 2020). Setti et al (2020) in a cohort study involving 427 oocyte recipient ICSI cycles showed that the abstinence period could affect embryo development and implantation. Moreover, in a prospective cohort study by Borges Jr et al (2019), data from 818 ICSI patients were analyzed and the results showed that the ejaculatory abstinence period could influence implantation and pregnancy rates.…”
Section: Multivariable Linear Regression Analysis Ofmentioning
confidence: 99%